An imidazolin-2-iminato ligand organozinc complex as a catalyst for hydroboration of organic nitriles. (16th October 2019) - Das, Suman; Bhattacharjee, Jayeeta; Panda, Tarun K.
Abstract : Catalytic hydroboration of nitriles with pinacolborane (HBpin) using the imidazolin-2-iminato zinc alkyl complex [{(Im t Bu N)Zn(CH2 CH3 )}2 ] (1c ) under mild and solvent-free conditions to afford corresponding diboronate esters in high yield is reported. Abstract : The reaction of diethylzinc with imidazolin-2-imines (Im R NH, R = Dipp (2, 6-diisopropylphenyl)), Mes (2, 4, 6-trimethylphenyl), and t Bu ( tert -butyl) afforded the corresponding dimeric zinc(ii ) imidazolin-2-iminato complexes [{(Im R N)Zn(CH2 CH3 )}2 ] (R = Dipp, 1a ; R = Mes, 1b ; R = t Bu, 1c ). The zinc complexes were characterised using spectroscopic techniques and the molecular structure of complex 1b was established by single-crystal X-ray diffraction analysis. Complex 1c was used as a catalyst for the chemo-selective hydroboration of organic nitriles with pinacolborane (HBpin) at ambient temperature to obtain diborylamines of a broad substrate scope in high yield. Zinc complex 1c exhibits a versatile substrate scope and good functional group tolerance for catalytic hydroboration reactions. A most plausible mechanism is proposed on the basis of the kinetic study.